1989
DOI: 10.1007/bf00934150
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of thromboembolism in hip-fracture patients

Abstract: In a prospective, double-blind, controlled study, we compared the antithrombotic efficacy of low-dose heparin with dihydroergotamine (A), low-molecular-weight heparin with dihydroergotamine (B), and placebo (C). Two hundred and thirteen patients surgically treated for fractures of the hip were randomly divided into three groups. One hundred and sixty-one patients were analyzed. All thrombi were verified by ascending phlebography. Nine patients died within 1 month after operation. A and B proved to be equally s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…We did not find any significant difference in DVTs between the pre-and postoperative start of prophylaxis, possibly due to the high exclusion rate. Other studies (5,11 ) claim that there is a two-puckle curve in the postoperative period, and undoubtedly the patients will benefit with prophylaxis for as long as possible, although this has not been proven significantly in any study. The low rate of DVT, only 8% proximal thrombi, indicates that thromboprophylaxis with Klexaneg is effective.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We did not find any significant difference in DVTs between the pre-and postoperative start of prophylaxis, possibly due to the high exclusion rate. Other studies (5,11 ) claim that there is a two-puckle curve in the postoperative period, and undoubtedly the patients will benefit with prophylaxis for as long as possible, although this has not been proven significantly in any study. The low rate of DVT, only 8% proximal thrombi, indicates that thromboprophylaxis with Klexaneg is effective.…”
Section: Discussionmentioning
confidence: 93%
“…Eight patients died during the study period. The (1)(2)(3)(4)(5)(6)(7)(8), but no study has been conducted with the aim of evaluating preoperative thromboprophylaxis. One study (8) applying preoperative phlebography proved 12% of patients developed DVT preoperatively.…”
mentioning
confidence: 99%
“…Thromboprophylaxis with LMWH in elective total hip replacement has been investigated in several trials and has been shown to be at least as efficient as standard heparin [8,9,11]. In patients undergoing emergency surgery for hip fractures, the prophylactic effect of LMWH on DVT has not been proven consistently [14,15]. The present trial compares the thromboprophylactic efficacy and the safety of a LMWH with that of dextran 70 in a well defined high risk population of patients with hip fractures.…”
Section: Discussionmentioning
confidence: 99%
“…[73] In addition, LMWHs have prolonged elimination half-lives, and following subcutaneous injections they have a much greater bioavailability than standard heparin. [77][78][79][80][81][82][83] The overall average risk reduction as compared with the combined estimate of the other treatment modalities was 52% (p <0.001) for LMWHs, with an incidence of postoperative DVT of approximately 15%. Since 1984, numerous randomised controlled clinical studies with LMWHs have been performed in various patient categories, including 7 in patients undergoing hip fracture surgery (table 1).…”
Section: Low Molecular Weight Heparinsmentioning
confidence: 99%